Feasibility study of engine oil concerning the kinematic viscosity, water contamination, and dissolved solids pollutants on locomotive CC 206 - Zulkarnain, Akbar; Saefullah, Dehar Bagas; Pratiwi, Damar Isti; Perwira, Dimas Adi; Dwipayana, Arif Devi; Arifin, Triana Sharly Permaisuri (Faculty of Engineering, Universitas Negeri Yogyakarta, 2025)
Lubrication can be defined as the provision of lubricating materials to a machine that aims to prevent direct contact between moving surfaces. Viscosity is a very important property in lubricating oil. Sampling of engine oil was carried out on locomotives CC 206 13 18 and CC 206 13 45 at Depo Lokomotif Sidotopo Daop 8 Surabaya. Testing of engine oil samples was carried out at the ITS Surabaya Laboratory and PT Sucofindo Surabaya based on ASTM D 445-97, ASTM D 95-13, and ASTM D 482 standards. The results of the test will be compared with the locomotive engine oil eligibility limit standard. From the tests carried out, it was found that the oil in CC 206 13 18 produced a kinematic viscosity of 15.86 cSt, water contamination of 0.07%, and dissolved solid pollutants of 0.973%. CC 206 13 45 produces a kinematic viscosity of 15.38 cSt, water contamination of 0.06%, and dissolved solid pollutants of 0.917%. From the tests on the two locomotives, it was found that the kinematic viscosity, water contamination, and dissolved solid pollutants of engine oil CC 206 13 18 and CC 206 13 45 are still within the limits of feasibility. Kinematic viscosity can affect the maximum mileage of the locomotive. The result on CC 206 13 18 is 186,962 km and on CC 206 13 45 is 194,352 km. So the oil can still be used beyond the manufacturer's specified distance limit.